Pendekatan Pembelajaran Tematik di SD / MI - Susilawati Rambe, Irasukma; Syaputra Nasution, Ledi; Sofiyah, Khotnah (PT. Alahyan Publisher Sukabumi, 2024)
The purpose of thematic learning in this elementary school environment is to provide and have distinctive characteristics that distinguish it from alternative educational approaches. The age group of school-age children, usually ranging from 6 to 12 years, is commonly referred to as the school period, indicating the transition from kindergarten to formal school. This phase is recognized as the appropriate period to acquire knowledge, given the child's emerging drive for achievement, although mainly through engaging in fun activities. Called the maturity period for school, this stage reflects the child's desire to acquire new competencies, which are ready to be offered by educational institutions. This research method uses a qualitative descriptive approach. Primary school children exhibit different characteristics, including natural curiosity and interest in their environment, a preference for fun activities, a tendency to explore and engage in new experiences, susceptibility to emotional influences that drive their actions, an aversion to dissatisfaction and failure, a tendency to learn effectively in a conducive environment, and a preference for learning through active participation, observation, initiative taking, and peer teaching.